2011
DOI: 10.1002/ejic.201100350
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure and Properties of Yb5Ni4Ge10

Abstract: The new compound Yb5Ni4Ge10 was obtained as single crystals in high yield from reactions run in liquid indium. Single‐crystal X‐ray diffraction data showed that it crystallizes in the Sc5Co4Si10 structure type in the tetragonal space group P4/mbm. The structure is a three‐dimensional framework of [Ni4Ge10] atoms with voids filled by Yb atoms. The Ni and Ge atoms form pentagons, hexagons, and octagons along the ab one‐dimensional plane, which are interconnected along the c axis via Ni–Ge–Ni zigzag chains. Magne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 31 publications
1
21
0
Order By: Relevance
“…Similarly, the average bond distance for the Yb3-Ge is 3.1754 Å, is also longer than the corresponding distance for Yb1-Ge and Yb2-Ge with 3.0175 and 2.9343 Å, respectively. Similar kinds of bonding behavior were observed in the mixed valent Yb 5 Ni 4 Ge 10 as well [2]. Since Katoh et al observed the mixed valent Yb in Yb 5 Co 4 Ge 10 based on the magnetic susceptibility measurements [22], our crystallographic data suggests the Yb1 and Yb2 atoms are mostly in the trivalent state and Yb3 in the divalent state.…”
Section: Crystal Chemistry Of Yb 5 Co 4 Ge 10supporting
confidence: 82%
See 2 more Smart Citations
“…Similarly, the average bond distance for the Yb3-Ge is 3.1754 Å, is also longer than the corresponding distance for Yb1-Ge and Yb2-Ge with 3.0175 and 2.9343 Å, respectively. Similar kinds of bonding behavior were observed in the mixed valent Yb 5 Ni 4 Ge 10 as well [2]. Since Katoh et al observed the mixed valent Yb in Yb 5 Co 4 Ge 10 based on the magnetic susceptibility measurements [22], our crystallographic data suggests the Yb1 and Yb2 atoms are mostly in the trivalent state and Yb3 in the divalent state.…”
Section: Crystal Chemistry Of Yb 5 Co 4 Ge 10supporting
confidence: 82%
“…As per Pearson crystallographic database [23] and inorganic crystal structure database [24], there are 37 compounds reported within the family of RE 5 T 4 X 10 compounds and are listed in Table 1. Among them only three were studied for the crystal structure from the single crystal XRD data, including our recent discovery of Yb 5 Ni 4 Ge 10 mixed valent Yb atoms [2]. However, the majority of these compounds were studied for their physical properties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Metal flux method has not only been proved to be a tremendous tool to grow single crystals of already known polycrystalline compounds for studying detailed physical properties but also been an effective way to explore completely new phases [11][12][13][14][15][16][17][18][19][20][21]. A classic example in this case is EuInGe.…”
Section: Introductionmentioning
confidence: 99%
“…Indium has been exploited even less as a synthetic flux medium than aluminum and gallium. Recently In metal was employed as a solvent for the synthesis of germanides Eu 2 AuGe 3 , 11 YbGe 3 , 12 Yb 4 TGe 8 , 5 Yb 5 Ni 4 Ge 10 , 13 where In acts as a non-reactive flux, as well as a number of intermetallic compounds in which In gets incorporated into the products including YbT In 5 (T = Co, Rh, Ir), 14 17 In this paper, we have used In as non-reactive flux for the crystal growth of EuGe 2 , EuCoGe 3 and Yb 2 AuGe 3 compounds. Semi-quantitative microprobe analyses of the samples were performed with a Hitachi S-3400 scanning electron microscope (SEM) equipped with an energy dispersive X-ray analyzer and phase identity and purity of samples were determined by powder XRD experiments carried out on a diffractometer using Cu Kα radiation.…”
Section: Methodsmentioning
confidence: 99%